Zebra alphaherpesviruses (EHV-1 and EHV-9): Genetic diversity, Latency and co-infections - Abdelgawad, Azza (2016)
Alphaherpesviruses are highly prevalent in equine populations and co-infections with more than one of these viruses’ strains frequently diagnosed. Lytic replication and latency with subsequent reactivation, along with new episodes of disease, can be influenced by genetic diversity generated by spontaneous mutation and recombination. Latency enhances virus survival by providing an epidemiological strategy for long-term maintenance of divergent strains in animal populations. The alphaherpesviruses equine herpesvirus 1 (EHV-1) and 9 (EHV-9) have recently been shown to cross species barriers, including a recombinant EHV-1 observed in fatal infections of a polar bear and Asian rhinoceros. Little is known about the latency and genetic diversity of EHV-1 and EHV-9, especially among zoo and wild equids. Here, we report evidence of limited genetic diversity in EHV-9 in zebras, whereas there is substantial genetic variability in EHV-1. We demonstrate that zebras can be lytically and latently infected with both viruses concurrently. Such a co-occurrence of infection in zebras suggests that even relatively slow-evolving viruses such as equine herpesviruses have the potential to diversify rapidly by recombination. This has potential consequences for the diagnosis of these viruses and their management in wild and captive equid populations.